Determination of soil bearing capacity and profile using CAP-SASW method at Western Malaysian Peninsular - Ramli, Ahmad Bukhari; Kasim, Norhidayu; Ismail, Norfarah Nadia; Ibrahim, Saerahany Legori; Md Husain, Nadiah; Wan Azahar, Wan Nur Aifa (Springer Nature, 2019)
Bearing capacity is one of an important feature in geotechnical engineering and estimated using in situ conventional method. Inherent problem in the method such as relieving of stress during drilling and testing motivates the use of seismic method to provide supplementary small strain parameters in estimating the bearing capacity. This paper presents a non-invasive method which offers sustainable development by utilizing the propagation of Rayleigh waves and thus minimizing cost in site investigation and construction work. Bearing capacity derived from an equation of hyperbolic shear stress-strain model to evaluate the bearing capacity at some of selected sites at western peninsular Malaysia.